(untitled) (Journal of Event, Tourism and Hospitality Studies, 2025)
Volunteer tourism has emerged as a dynamic form of travel that offers youths opportunities for personal development and social impact. However, the developmental and transformational needs of youth involved in volunteer tourism remain underexplored, especially in rapidly developing urban contexts like Ho Chi Minh City. This study aims to investigate the personal development and transformation needs of young individuals in Ho Chi Minh City, with a particular focus on factors such as gender, occupation, and income. The research used a quantitative approach, surveying 522 youths and analyzing their motivations, developmental needs, and the influence of demographic factors on those demands. The findings reveal that young participants are strongly driven by a desire for personal growth, particularly in soft skill enhancement, self-awareness, and meaningful engagement with local communities. Importantly, the study uncovers significant variations in development needs across demographic lines, emphasizing the necessity for inclusive, tailored program designs. Beyond skill acquisition, the data suggest that volunteer tourism plays a critical role in fostering reflective global citizenship and pro-social behavior. By situating personal transformation at the heart of volunteer tourism, this research contributes to both theory and practice, offering new insights into how service-oriented travel can shape empowered, socially conscious youth in rapidly urbanizing contexts.